2015
DOI: 10.1073/pnas.1409563112
|View full text |Cite
|
Sign up to set email alerts
|

Loss of autophagy causes a synthetic lethal deficiency in DNA repair

Abstract: (Macro)autophagy delivers cellular constituents to lysosomes for degradation. Although a cytoplasmic process, autophagy-deficient cells accumulate genomic damage, but an explanation for this effect is currently unclear. We report here that inhibition of autophagy causes elevated proteasomal activity leading to enhanced degradation of checkpoint kinase 1 (Chk1), a pivotal factor for the errorfree DNA repair process, homologous recombination (HR). We show that loss of autophagy critically impairs HR and that aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 32 publications
11
118
0
Order By: Relevance
“…Therefore, we monitored HR using the direct-repeat (DR)-GFP reporter and NHEJ using the pEJ5-GFP reporter. As shown in Figures 6A, 6B, S5A, and S5B, consistent with a previous report (Liu et al, 2015), autophagy inhibition reduced the efficiency of HR, but not NHEJ. More importantly, the reduction could be rescued by p62 knockdown (Figures 6A, 6B, S5A, and S5B), indicating that autophagy impairs DNA repair in a p62-dependent manner.…”
Section: Loss Of Autophagy Leads To a Deficiency Of Chromatin Ubiquitsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we monitored HR using the direct-repeat (DR)-GFP reporter and NHEJ using the pEJ5-GFP reporter. As shown in Figures 6A, 6B, S5A, and S5B, consistent with a previous report (Liu et al, 2015), autophagy inhibition reduced the efficiency of HR, but not NHEJ. More importantly, the reduction could be rescued by p62 knockdown (Figures 6A, 6B, S5A, and S5B), indicating that autophagy impairs DNA repair in a p62-dependent manner.…”
Section: Loss Of Autophagy Leads To a Deficiency Of Chromatin Ubiquitsupporting
confidence: 92%
“…In our study, we found that p62 regulates both NHEJ and HR, although autophagy inhibitor only suppresses HR ( Figures 6A and 6B). It was recently reported that loss of autophagy leads to a defect in DSB repair by HR by reducing Chk1 abundance and phosphorylation (Liu et al, 2015). However, in our system, p62 did not affect Chk1 status, suggesting that p62-impaired DNA repair may rely on another pathway (for example, RNF168) ( Figures S5C-S5E).…”
Section: Rnf168 and P62mentioning
(Expert classified)
See 1 more Smart Citation
“…The two major pathways for repair of DSBs are homologous recombination (HR) and nonhomologous end joining (NHEJ). Consistent with a previous report, 8 autophagy inhibition reduced the efficiency of HR but not NHEJ. More importantly, this reduction could be rescued by p62 knockdown, indicating that autophagy impairs DNA repair in a p62-dependent manner.…”
supporting
confidence: 93%
“…Enforced p62 accumulation induces ROS production, DNA damage, aneuploidy, and tumorigenesis (84). Furthermore, inhibition of autophagy leads to increased proteasomal activity and results in enhanced degradation and reduced abundance of Chk1, an essential factor for homologous recombination, and to a corresponding deficit in DNA repair of double-strand breaks (85).…”
Section: Atg7 Mediates Negative Feedback Regulation Of Foxo1mentioning
confidence: 99%